The Blockchain Technology From Maqasid Shariah Perspective - Yusof Mahmoud Aljamos; Azman Mohd Noor; Mohamad Shafiq Mohd Aswadi; Ahmad Syukran Baharuddin (Maqasid Institute., 2024)
Non-Indexed Publication